Polyamines in fungi : their distribution, metabolism, and role in cell differentiation and morphogenesis /: their distribution, metabolism, and role in cell differentiation and morphogenesis. (2015) - Valdés-Santiago, Laura; Ruiz-Herrera, José
No abstract available